How Positive Word-of-Mouth (Electronic and Face-to-Face) is Influenced by The Quality of Customer Relationships in The Telecommunications Industry - Danendra, Ariel Belva; Rahayu, Siti; Widjaja, Fitri Novika (LP3M Universitas Putra Bangsa, 2024)
This research aims to advance knowledge about the influence of positive behavior from mouth to mouth (WOM) electronically and face-to-face by testing the model of correlation between the quality component of relationship (RQ) and anteseden in the telecommunications service environment with the moderation of Positive Emotional Experience. The study was conducted in one service setting, and thus, the results could not be generalized. The data collected to support the initial variable is distributed to users of telecommunications networks in Indonesia through the Google Forms questionnaire form. This investigation uses SmartPLS 4 because of its durability in testing predictive models. This paper provides guidance on how telecommunications service managers can develop and manage their relationship network. Specifically, this paper shows how business references can be generated and used to build customer retention from various relationship-building strategies. This study shows that service providers that provide quality services, design superior values and provide reliable information are in a better position to develop good relationships with customers and ultimately engage them in a Positive Emotional Experience.